2017
DOI: 10.24014/jupet.v14i2.3676
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Semen Cair Sapi Simental Menggunakan Larutan Isotonis Komersial Pada Konsentrasi Dan Lama Penyimpanan Berbeda

Abstract: Artificial insemination (AI) is a technique to insert the sperm or semen of bull thawed and processed first into the genital tract of female methods and a special tool called insemination gun, efforts to optimize the management of the cement in order to obtain the quality of cement is optimal to do with the selection of diluent cement. One alternative materials cement diluent is an isotonic solution Commercial (LIK). This study aimed to examine the interaction between the concentration and duration of storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Observation data showed that the longer storage time decreased the sperm viability percentage value. Mardian et al (2017) suggest that the length of storage for the sperm cells may decrease viability and motility value due to the increased lactic acid as the result of cell metabolic processes during storage. The increased lactic acid becomes toxic, causing the sperm death.…”
Section: Resultsmentioning
confidence: 99%
“…Observation data showed that the longer storage time decreased the sperm viability percentage value. Mardian et al (2017) suggest that the length of storage for the sperm cells may decrease viability and motility value due to the increased lactic acid as the result of cell metabolic processes during storage. The increased lactic acid becomes toxic, causing the sperm death.…”
Section: Resultsmentioning
confidence: 99%